Editorial: Navigating modern challenges: Integrating Islamic Ethics in philanthropy, consumer behavior, and organizational practice. - Hendryadi, Hendryadi (LPMP Imperium, 2023)
This issue of Serambi Journal (Vol 5, No. 2, 2023) presents a multifaceted exploration of Islamic ethical principles applied to contemporary economic and organizational challenges. The collection features five groundbreaking studies that examine Indonesia's philanthropic landscape, the interplay between scarcity marketing and Islamic religiosity in consumer behavior, the role of Islamic work ethics in promoting employee voice behavior, the connection between financial well-being and compulsive buying among students, and the adaptive application of al-Ujrah principles during the COVID-19 pandemic. Together, these studies demonstrate the enduring relevance of Islamic values in addressing modern socioeconomic issues while offering practical insights for enhancing organizational effectiveness, promoting responsible consumption, and strengthening community resilience through Islamic frameworks.